2005
DOI: 10.1080/14681990500142004
|View full text |Cite
|
Sign up to set email alerts
|

Partnering and parenting expectations in adoptive couples

Abstract: This paper describes research investigating couples who undertook the procedure of becoming adoptive parents, studying the partners' representations of relationships in the context of their psychological sense of loss owing to infertility. The sample consisted of 100 subjects (50 couples) who took part in an assessment process related to adoption within the Social Services structures. The subjects had the following features in common: they were between 35 and 45 years of age; the duration of their marriages wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
4
25
0
1
Order By: Relevance
“…The great majority of pre-adoptive couples had a secure attachment style (84%) and showed high relational adjustment (87%); this finding suggests that most future adoptive parents may be well equipped to face with the challenges and the opportunities of the adoption experience (Cavanna et al, 2008). In synthesis, the few extant studies on the pre-adoptive phase portray prospective adoptive parents as resourceful and more secure in their attachment when compared to couples where a child is born to them (Cavanna et al, 2008(Cavanna et al, , 2011Levy-Shiff et al, 1990Santona & Zavattini, 2005;Schechter, 1970). However, other researchers have highlighted, from empirical and theoretical viewpoints, difficulties and relational vulnerabilities of parents in the pre-adoptive phase (Brodzinsky & Huffman, 1988;Caballo et al, 2001;Fontenot, 2007;Levy-Shiff et al, 1991;Priel, Melamed-Hass, Besser, & Kantor, 2000;Santona & Zavattini, 2005).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The great majority of pre-adoptive couples had a secure attachment style (84%) and showed high relational adjustment (87%); this finding suggests that most future adoptive parents may be well equipped to face with the challenges and the opportunities of the adoption experience (Cavanna et al, 2008). In synthesis, the few extant studies on the pre-adoptive phase portray prospective adoptive parents as resourceful and more secure in their attachment when compared to couples where a child is born to them (Cavanna et al, 2008(Cavanna et al, , 2011Levy-Shiff et al, 1990Santona & Zavattini, 2005;Schechter, 1970). However, other researchers have highlighted, from empirical and theoretical viewpoints, difficulties and relational vulnerabilities of parents in the pre-adoptive phase (Brodzinsky & Huffman, 1988;Caballo et al, 2001;Fontenot, 2007;Levy-Shiff et al, 1991;Priel, Melamed-Hass, Besser, & Kantor, 2000;Santona & Zavattini, 2005).…”
mentioning
confidence: 97%
“…In synthesis, the few extant studies on the pre-adoptive phase portray prospective adoptive parents as resourceful and more secure in their attachment when compared to couples where a child is born to them (Cavanna et al, 2008(Cavanna et al, , 2011Levy-Shiff et al, 1990Santona & Zavattini, 2005;Schechter, 1970). However, other researchers have highlighted, from empirical and theoretical viewpoints, difficulties and relational vulnerabilities of parents in the pre-adoptive phase (Brodzinsky & Huffman, 1988;Caballo et al, 2001;Fontenot, 2007;Levy-Shiff et al, 1991;Priel, Melamed-Hass, Besser, & Kantor, 2000;Santona & Zavattini, 2005). Moreover, it is a common clinical experience for adoptive parents to face challenges related to anger, anxiety, low self-esteem, and the envy of fertile couples conjunctly with the mourning of their own chance to bear children.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In light of these findings, empirical studies have also shown that adoptive couples Downloaded by [University of Western Ontario] at 01:40 09 February 2015 may face certain marital stressors that are uniquely related to these tasks of the adoption life cycle. Many couples who adopt also have struggled with infertility, which may affect their relationship in a number of ways (Santona & Zavattini, 2005). If one partner is infertile and the other is not, the one who is infertile may feel guilty, while the other spouse may feel anger over the situation of childlessness and ask, "What if I had married someone else (or did in the future)?"…”
Section: Adoption and Marriagementioning
confidence: 99%
“…A study of social workers providing adoption preservation services found that couples often had unequal commitments to the adoption, resulting in tension when difficulties with a child arose (Smith, 2006). Adoptive couples must manage information about their children as well as sometimes help them to deal with the trauma of previous experiences (Santona & Zavattini, 2005).…”
Section: Adoption and Marriagementioning
confidence: 99%